What factors determine membership to farmer groups in Uganda? Evidence from the Uganda Census of Agriculture 2008/9 - (:unkn) unknown (Economic Policy Research Centre (EPRC), 2012)
While government of Uganda and its development partners are targeting farmer groups as the vehicle for agricultural development, there is limited empirical evidence on what drives membership to these groups. Using the Uganda Census of Agriculture 2008/9 data, this paper reveals low levels of membership both at individual and household levels with a marked regional dimension. The key policy variables found to influence participation in farmer group included education attainment, distance to extension service and quality of road infrastructure. Increasing membership to farmer groups requires government and its development partners to target more resources towards less educated farmers and those who live far from extension workers. The use of the local language in publicity materials is also important in ensuring participation among the illiterate and the less educated. Overall, there is a need for concerted efforts by all institutions supporting groups to ensure that existing groups have improved access to agricultural technologies and noticeable outcomes are achieved so as to attract more farmers.
Keywords: Farmer group Membership; Decision Making; Uganda Census of Agriculture